Moral Taste and Moral Education - An Interview Study - Niclas Lindström; Lars Samuelsson (Athens Institute for Education and Research, 2022)
In recent research on moral psychology, the human consciousness has been compared to a tongue, with different taste buds, which together can cause a variety of sensations. According to this theory, people in general have a preparedness to react to situations, which can provide opportunities or pose threats in a social context. Moral psychologist, Jonathan Haidt, has described these receptors as pairs, for example: care/harm, fairness/cheating, loyalty/ betrayal, authority/subversion and sanctity/degradation. Which of these foundations the individual develops a taste for depends, largely, on the social and cultural context. Hence, the choices teachers make of which issues to address and in what way can contribute to a learning environment that influences their pupils' moral outlook. The purpose of this study is to investigate which of these moral intuitions or taste preferences that teachers want to endorse and cultivate in their pedagogical practices. Against this background, a number of qualitative research interviews were conducted with experienced teachers in the non-confessional subject religious education (RE), who have a particular responsibility for moral education in the Swedish school system. The interviews were based on a modified version of the Moral Foundations Questionnaire, which was deliberately developed to determine the participants' moral taste, and the participants were asked to elaborate their answers. The results indicate that the participants tended to favour harm and fairness over loyalty, authority and sanctity. As one of the participants puts it: "many of my examples relate to the weak and vulnerable or the ones that are denied their rights in society... these pedagogical choices are based on the content of the curriculum but also mirror my own preferences". In this paper we analyse the interviews with the RE teachers and critically discuss the consequences the moral foundations theory has for moral education. Keywords: moral education, ethics education, moral psychology, moral foundations theory